Genetic Characteristics of Actinomycetes Isolates (GST, KP, KP11, Kp16, T24, T37 Code) by RFLP of NRPS Genes - Melati Aprilliana Ramadhani; Nanik Sulistyani (Universitas Ahmad Dahlan, 2015)
Actinomycetes is the one of antibiotic producing microorganisms. Actinomycetes isolates with GST, KP, KP11, KP16, T24, T37 have been isolated from soil. This study aims to determine the diversity of actinomycetes isolates by RFLP (Restriction Fragment Length Polymorphism) of NRPS (Non Ribosomal Peptide Synthetase) genes from GST, KP, KP11, KP16, T24, and T37 isolates. This study is divided into several steps of the DNA isolation from isolate GST, KP16, T24, T37, KP, KP11, PCR of the 16S rRNA and NRPS genes and cutting the NRPS genes fragmens with HaeIII enzyme to determine the diversity of isolates. Results of DNA isolate, PCR of 16S rRNA genes and NRPS genes, and RFLP of NRPS genes performed by agarose gel electrophoresis. The diversity of the isolates were analyzed by multivariate analysis UPGMA with MVSP 2.0 applications. The results showed the diversity of 6 actinomycetes isolates are T37 and GST have 64 % similarity, KP11 and KP16 have 96 % similarity, KP has 76 % similarity with KP11 and KP16, while T24 has 60 % similarity with KP and 12 % similarity with T37 and GST. Based on RFLP analysis of the NRPS genes, among of 6 isolates can divided into 4 groups are T37 and GST isolates as group 1, KP11 and KP16 isolates as group 2, KP isolate as group 3, and T24 isolate as group 4.